Liver Micro-Circulator Back After Its Partial Resection For 15 Day Of Life - Askarov T.A., Olimkhujayev F.Kh., Akhmedov M.D., Fayziev Y.N., Ashurmetov A.M. (International Journal of Advanced Science and Technology, 2020)
In an experiment on 180 white mongrel male rats, 31-34% (left lateral lobe) of the liver was resected on the 15th day of life. We found that after resection of the liver, constantly occurring liver complexes were detected, which consist of 3 types of lobules. The initial link of blood outflow from the hepatic lobes is the initial hepatic venules, which are formed from the fusion of sinusoids in the subcapsular zone of the liver. After resection, the main process is the formation of new structural and functional units – liver lobes in the subcapsular area of the organ.